Adaptation to Third-Party Payments: Statistical Analysis of Digital Donations Made to Donglin Monastery - Liu, Qi (Religions (Basel, Switzerland ), 2024)
This paper explores the adaptations Buddhism has made to digital payment methods in the context of the Chinese mainland. To provide the audience with a relatively comprehensive understanding of the general context in which the new method of donation is applied, this paper first introduces the development and digital landscape of the internet and third-party payments in the Chinese mainland. Then, statistical analysis is used to make large-scale claims by analyzing 1328 donation records made to Donglin Monastery in Mount Lu with the statistical software SPSS to determine whether the digital donation method is linked to the purpose of donations, or the amount of money being donated, and to what extent it substitutes for traditional donation methods.